PENGELOLAAN TANAH ASSET PEMERINTAH KOTA SURABAYA - Urip Santoso (Yuridika, 2010)
Land assets status Surabaya City Government is Right to Use and Right of Management. If a Right to Use, then the authority is to use the land for the benefit of its duties. If a Right of Management, the authority is handed over portions of land management rights to third parties. Forms of land use Surabaya City Government assets by third parties in the form Land Use Permit and Land Use Submission Agreement. Land Use Permit birth right to use land, while the Land Use Submission Agreement birth Right of Building.